Surgical removal of intravascular leiomyomas with intracardiac extension: A two-case report (2020)
Leiomyomatosis is a uterine condition that can rarely present with extrauterine involvement. Intravenous and intracardiac extensions are extremely rare presentations and, in these cases, the intra-cardiac mass may be confused with a cardiac myxoma and can be associated with pulmonary embolism. Here we report two cases of successful surgically removed intracardiac leiomyomas under cardiopulmonary bypass. © 2020 Wiley Periodicals, Inc.